The Relationship of Mental Fatigue (Flim) With the Level of Hormone Cortisone and the Performance of Running (100) Meters for Young Players - Hayder Naji Habash Alshawi (Journal of Global Pharma Technology, 2017)
Mental fatigue works to produce cortisone, which causes a series of reactions in the body, including weakness of the immune system and tension in the large muscles ,high blood pressure, and the recurrence of the high rate of cortisone, which leads to the death of brain cellsespecially in the area which is called the hippocampus, an area necessary for memory .(1)The events of the track and the field require special requirements of physical specifications and physical abilities in addition to the training methods for each of the effectiveness of the success and from these events that require a high level of the effectiveness of running 100 meters .(2)The problem of research was that the work of hormones in the body of the important topics in the field of sports physiological psychology in general and in the track and field activities, especially the activity of 100 meters .(3)The problem of looking for the work of hormones in the body of important topics in the field of sports physiological psychology in general and in the arena and field activities, especially the effectiveness of 100 meters ,As the interest of researchers focused on the development of physical abilities, planning and skill and lack of attention to the psychological aspect, which greatly affects the achievement, despite its importance, which is considered the dominant side of the rest of the capacity and mental fatigue of the nervous system and its relationship to achievement and its effects on the secretion of cortisol is considered these variables that affect The players of the effectiveness of the 100 m and therefore affect the results of achievement because the fatigue that gets to the players during fatigue will reduce the activity of the nervous system and therefore cannot show the player all his abilities and do not reach the desired achievement and poor performance So wanted researchers conducting this study, an attempt to achieve the best results using a test of the tests Vienna system (mental fatigue FLIM) and its relationship to the level of the hormone cortisol, and the aim of the research to identify the relationship between mental fatigue and the level of the hormone cortisone and the performance in the 100 meters running for young player. The researchers used the descriptive approach in the method of interrelationships to suit the nature of the problem on the players of the 100 meters advanced to the clubs of Iraq and were selected in a comprehensive inventory, tests used in research, test (mental fatigue) .The researchers concluded that there was a significant correlation between mental fatigue (frequency of fusion) (VF) and cortisone concentration as well as performance ,in addition, there is a significant correlation between mental fatigue (frequency of flashes) (FF) and the level of hormone cortisone and performance . The researchers recommend that the coach to pay attention to knowledge of the values of mental fatigue to the players in addition to knowing the levels of hormones in order to be able to address the problems facing players and how to overcome them ,as the high rate of cortisone evidence of tension in the player and the duty of the coach to address the excitement and tension of the players being a negative impact on their performance .Keyword: Mental fatigue, Hormone cortisone, Performance and running